Stability Evaluation Of Chicken Nuggets Formulated With Fibres - ZAINOL ABIDIN, NURUL AKHMA (Enhanced Knowledge in Sciences and Technology, 2021)
The plant dietary fibre that included bamboo shoot powder (BSP), coconut powder (CP) and modified tapioca starch was used in the chicken nuggets to act as fat replacer. The formulated chicken nugget and the standard nuggets were studied for their storage stability in term of pH, moisture content, microbiological analysis and sensory quality during storage at (4±1℃). The values of pH and moisture content decreased significantly (p<0.05). The total plate count (TPC) were observed and increase significantly during the storage period. The sensory attributes were not significantly changed across time. With the result obtained, it is concluded that nuggets that incorporated with BSP, CP and MTS. Based on the results obtained, it is concluded that nuggets incorporated with fibre do have a similar pattern of quality losses during the storage period with the standard chicken nugget that has preservatives.